Urban outdoor thermal comfort in western China. Issue 2 (4th March 2021) - Zhen, Meng; Dong, Qi; Chen, Ping; Ding, Wei; Zhou, Dian; Feng, Wei
ABSTRACT: Outdoor space is essential for urban residents' daily activities, and thermal comfort is an important indicator to evaluate these places. Currently, there are few studies on city outdoor thermal comfort in western China. This paper, by use of weather stations and questionnaires, studies the relationship between outdoor thermal comfort, adaptive thermal comfort, residents' social characteristics, and the thermal comfort in Xi'an. In the spring, "neutral" is the most commonly perceived thermal sensation (44.19%), followed by slightly uncomfortable (31.4%). Air temperature is the most important meteorological parameter affecting thermal sensation vote, followed by solar radiation. The thermal acceptable range in Xi'an is 2.69 32.10°C, and the neutral temperature is 17.40°C. In terms of social status, young people (age≤20) have the highest heat sensitivity, while the middle-aged (20< age≤40) have the lowest. And women's heat sensitivity is higher than that of men. By comparing the thermal comfort ranges of Xi'an, Tianjin, and Harbin, it is found that thermal comfort shows regional and climatic differences. Graphical Abstract: uf0001